Schrift- und Schreibmystik. Christina von Hane - Suerbaum, Almut M. V. (Oxford University, 2014)
The subject of my thesis is a little-studied hagiographical work that gives important insights into rewriting processes and their significance in medieval textual culture. The anonymous Life of Christina of Hane, a thirteenth-century Premonstratensian nun from the Palatinate, is an example of bridal
Keywords: 👤 christina of hane

Christine von Retters (? um 1291) - Sauser, Ekkart (Biographisch-bibliographisches Kirchenlexikon, 2003)
Keywords: 👤 christina of hane